The First Molybdenum(VI) and Tungsten(VI) Oxoazides MO2(N3)2, MO2(N3)2⋅2 CH3CN, (bipy)MO2(N3)2, and [MO2(N3)4]2− (M=Mo, W)1. Issue 33 (15th July 2015) - Haiges, Ralf; Skotnitzki, Juri; Fang, Zongtang; Dixon, David A.; Christe, Karl O.
Abstract Molybdenum(VI) and tungsten(VI) dioxodiazide, MO2(N3)2 (M=Mo, W), were prepared through fluoride–azide exchange reactions between MO2F2 and Me3SiN3 in SO2 solution. In acetonitrile solution, the fluoride–azide exchange resulted in the isolation of the adducts MO2(N3)2⋅2 CH3CN. The subsequent reaction of MO2(N3)2 with 2, 2′‐bipyridine (bipy) gave the bipyridine adducts (bipy)MO2(N3)2. The hydrolysis of (bipy)MoO2(N3)2 resulted in the formation and isolation of [(bipy)MoO2N3]2O. The tetraazido anions [MO2(N3)4]2− were obtained by the reaction of MO2(N3)2 with two equivalents of ionic azide. Most molybdenum(VI) and tungsten(VI) dioxoazides were fully characterized by their vibrational spectra, impact, friction, and thermal sensitivity data and, in the case of (bipy)MoO2(N3)2, (bipy)WO2(N3)2, [PPh4]2[MoO2(N3)4], [PPh4]2[WO2(N3)4], and [(bipy)MoO2N3]2O by their X‐ray crystal structures.